Novel Strategies in C-H Oxidations for Natural Product Diversification—A Remote Functionalization Application Summary - Junrong, Huang; Min, Yang; Chuan, Dai; Yajun, Zhou; Huilong, Fang; Lizhi, Zhu; Feng, Yin; Zigang, Li (Frontiers in Chemistry, 2021)
Selectively activating the distal inactive C-H bond for functionalization is one of the on-going challenge in organic synthetic chemistry. In recent years, benefiting from the development of selective synthesis methods, novel methodologies not only make it possible to break non-traditional chemical bonds and attain more diversity in inactive sites, but also provide more possibilities for the diversification of complex natural products. Direct C-H bond functionalization approaches make it feasible to explore structure-activity relationship (SAR), generate metabolites and derivatives, and prepare biological probes. Among them, direct oxidation of inert C-H bonds is one of the most common methods for natural product diversification. In this review, we focus on the application of remote functionalization of inert C-H bonds for natural products derivatization, including the establishment of oxidation methods, the regulation of reaction sites, and the biological activities of derivatives. We highlight the challenges and opportunities of remote functionalization of inert C-H bonds for natural product diversification through selected and representative examples. We try to show that inert C-H bond oxidation, properly regulated and optimized, can be a powerful and efficient strategy in both synthetic and medicinal chemistry.